A brief survey on agricultural robots - Behmanesh, Mohammad; Tang, Sai Hong; Mohd Kassim, Muhamad Saufi; Azim Farhad, Arsalan; Dashtizadeh, Zahra (International Journal of Mechanical Engineering and Robotics Research, 2020)
Agriculture has always been one of the most important issues for humankind. During past decades while robotics technologies have been introduced to many industries, agricultural scientists also made advantages of it and improved agricultural methods and products. In this paper the main advantages of the robotics in agriculture by far is presented. The robots that have been used in agricultural researches can be categorized in 4 main types; path navigators, harvesting robots, crop disease detectors and weed detectors which are studied in this paper.